Taking heart rate variability to the next level in sports: towards a multi-signal integration - Bourdillon, N.; Millet, G. P. (Frontiers in Sports and Active Living, 2026)
Heart rate variability (HRV) is most often used as a standalone, without integration of complementary data. Yet these data are at our fingertips, and a revolution might be just around the corner. This perspective article gives insight on how integrating accelerometery and continuous blood pressure and extracting ventilatory variables may improve the use of HRV, taking it to a whole new level for elite and recreational sports, assessing fatigue, and intensity domains. Also, the use of mass data could lead to seamless measurements as precise and relevant as in elite sports, which could be made available to the public for health assessment and follow-up.